MEDIA PEMBELAJARAN DESAIN WEB MENGGUNAKAN PHOTOSHOP CS6 DAN ADOBE DREAMWEAVER BERBASIS MULTIMEDIA - Ahmad Surahmat; Sukarta Atmaja (Jurnal Sistem Informasi dan Informatika (Simika), 2019)
In designing a beautiful and attractive web, for ordinary people it certainly looks very difficult. So from that the advantage of learning to use learning media using multimedia is that people can see firsthand how and the steps? And the results of how they are made can be seen immediately. Compare this with a book that has a step by step guide, but people will feel confused because not a few books give results that are not in accordance with the method. Learning media that will be displayed in the form of a website display. With the help of Photoshop CS6 and Adobe Dreamweaver application we can make web display easier and also create websites without direct contact with the programming language. Multimedia-based learning aims to facilitate students in understanding each method of web design techniques. In this study discussed how to design web using Photoshop CS6 with the help of slice tool. Multimedia-based web design learning media uses three methods, namely web designing in Photoshop CS6, adding code with Adobe Dreamweaver, and making learning videos using Camtasia Studio 8, the learning videos produced can be seen with the .wav .flv .swf format with CD quality, DVD. The results of this study were conducted to develop multimedia-based learning media so that the material delivered was easier to understand.